PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN PERILAKU PEMBERIAN PIJAT BAYI OLEH IBU DI BRAJAN TAMANTIRTO BANTUL YOGYAKARTA - Ekawati, Ekawati; Anggraini, Tyasning Yuni Astuti (Media Ilmu Kesehatan, 2018)
Background: Baby massage is the oldest known human touch therapy and the most popular. Baby massage not only affects the babys physical and emotional growth. If baby massage done by his father, it can increase milk production in the mothers body. Objective: Knowing mothers knowledge and behavior about infant massage before and given health education and improvement of knowledge and behavior before and after counseling. Methods: Type of research that will be used in this research is pre-experiment design (pre-experiment design). The sample size is 30 respondents. Data source in this research is primary data source that is by using questioner and Prior to being given a health education about infant massage. Result : Knowledge of the majority mother either as many as 19 respondents (63,33%), after being given health education about baby massage, all knowledge of good mother (100%), before given health education about baby massage, infants as a whole fall into the category of less (100%) because all mothers do not yet know how to do baby massage, after being given health education about baby massage, mother behavior in doing baby massage majority according to technique that is 17 responden (56,67%). Conclusion: There is a significant influence between health education on infant massage on mothers knowledge and behavior about baby massage in Brajan Tamantirto Banul Yogyakarta   Keyword: Baby massage behavior, health education, knowledge.